Psychotherapeutic Intervention Plan to Reduce the Emotional Effects of Empty Nest Syndrome in Older Adults - Guadalupe-Tixi, Paola (2024)
Introduction: Empty nest syndrome is a psychological disorder that carries significant emotional implications for parents when their children leave home. Common experiences include anxiety, depression, lack of coping strategies and family dysfunctionality. Objective: The purpose is to design a psychotherapeutic intervention plan aimed at mitigating the emotional effects of empty nest syndrome in older adults. Material and methods: A descriptive-exploratory study was carried out with a quantitative approach, using a pretest design. The sample, consisting of 100 adults over 65 years of age, was selected by convenience sampling. A questionnaire including demographic variables was designed and tests such as the Mini Mental, Yesavage, Family Apgar, Hamilton-Anxiety and CAE Coping were applied. The data were analyzed with the statistical software SPSS V 22.00 and Stata 17.0. Results: Significant differences were observed in emotional indicators and other sociodemographic variables, particularly in depression, family dysfunction, lack of coping and anxiety (P > 0.05). Likewise, age, sex, residence and marital status were found to exert a significant influence (P > 0.05). Conclusion: The psychotherapeutic intervention plan emphasizes the importance of improving health, lifestyles and family dynamics, as well as promoting the integration of the elderly into society.